Effect of new polyherbal formulations DF1911, DF2112 and DF2813 on CFA induced inflammation in rat model - Bhagyashri Nagarkar; Suresh Jagtap (BMC, 2017)
Abstract Background Aim of the present study was to evaluate anti-inflammatory activity of newly developed polyherbal formulations DF1911, DF2112 and DF2813. These newly developed formulations are modifications of Dashamoola, a well known Ayurvedic formulation, along with addition of new plants. Methods Complete Freund's adjuvant (CFA) induced inflammation in rat was used as an experimental model. Effects of the treatment in rats were monitored by physiological and biochemical parameters, histopathology and through gene expression studies. Results Diclofenac sodium showed maximum percentage inhibition (56.8 ± 3.5%) of paw edema followed by Dashamoola Kwatha (19.9 ± 1.8%). Among test formulations treated groups, DF1911 at 250 mg/kg bw (48.2 ± 5.4%, p < 0.001) and DF2112 at 250 mg/kg bw (49.9 ± 3.5%, p < 0.001) showed significant and maximum increase in percentage inhibition of paw edema as compared to Dashamoola Kwatha. Hematological alterations in CFA rats were normalized after treatment with test formulations. Results of serum markers and histopathological observations also supported the activity of formulations. Increased MDA levels in liver tissue of CFA injected animals significantly (p < 0.05) decreased by Diclofenac sodium and test formulation treated groups. DF1911, DF2112 and DF2813 showed down-regulation of IL1-β (~6.4-fold, ~5.2-fold and ~7.6-fold), IL-6 (~1.1-fold, ~1.6-fold and ~1.9-fold), TNF-α (~2.0-fold, ~4.6-fold and ~3.5-fold), and iNOS (~1.2-fold, ~1.8-fold and ~1.1-fold) in inflamed paw tissue compared to negative control group, respectively. Conclusions The anti-inflammatory effects of DF1911 and DF2112 in rats were significantly higher than the Dashamoola Kwatha and are comparable to Diclofenac sodium.